Numerical simulation of tsunamis generated by landslides on multiple GPUs. (September 2016) - de la Asunción, M.; Castro, M.J.; Mantas, J.M.; Ortega, S.
Highlights: We propose a 2D numerical scheme to simulate tsunamis generated by landslides. A description of an MPI-CUDA implementation which uses overlapping techniques. Validation of the numerical scheme by simulating a real tsunami. Load balancing algorithms to balance the computational load in wet and dry areas. Good weak and strong scaling using up to 24 GPUs in real and artificial problems. Abstract: In this work we propose a two-layer Savage–Hutter type model that is the natural extension of the 1D system proposed by E. D. Fernández-Nieto et al in 2008 to simulate tsunamis generated by landslides. We describe a single GPU and a multi-GPU implementation of this model using MPI and the CUDA framework over structured meshes. The distributed implementation is tested for several artificial and realistic problems using up to 24 GPUs. We also propose a static and a dynamic load balancing algorithm in order to deal with the unbalanced computational load due to different amount of wet and dry areas among the subdomains. The validity of the model is tested by simulating the tsunami occurred in Lituya Bay, Alaska, in 1958. Numerical experiments show the efficiency of the multi-GPU solver, the usefulness of the load balancing algorithms and the validity of the model to simulate real tsunamis generated by landslides.